Strategic Analysis of Accelerating the Reduction of Stunting Prevalence in Kuantan Singingi Regency Using the SWOT Approach and IFAS–EFAS Matrix - Sarwendah; Herniwanti (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Stunting remains a significant public health problem in Kuantan Singingi Regency, Riau Province, with a relatively high prevalence influenced by nutritional, environmental, and behavioral factors. This study aimed to analyze strategies to accelerate the reduction of stunting prevalence in Kuantan Singingi Regency using a SWOT approach and the IFAS–EFAS matrix. This was a descriptive-analytic study with a cross-sectional design employing SWOT analysis. Primary data were collected through in-depth interviews and observations with key informants from public health units, nutrition, environmental health, and health promotion. Secondary data were obtained from health profiles, stunting reports, and sanitation coverage data. Strategic analysis was conducted using SWOT analysis supported by the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The IFAS calculation produced a score of −9.4, the EFAS calculation yielded −6.9; this negative value indicates that the external opportunities supporting WASH–stunting in Kuantan Singingi Regency are also weak, because external threats are far greater than external opportunities. Furthermore, based on the IFAS and EFAS results, strategic positioning for accelerating stunting reduction was mapped onto the SWOT quadrant diagram. The SWOT quadrant shows that the coordinate point (−9.4; −6.9) falls in Quadrant IV (Weakness–Threat), indicating the dominance of internal weaknesses and external threats in accelerating stunting reduction. This position suggests that the most appropriate approach is a defensive strategy: addressing mothers’ low knowledge through education delivered by health centers (puskesmas) and community health volunteers (cadres); establishing a routine schedule for counseling, home visits, and cadre-based education activities led by environmental health cadres; strengthening monitoring and evaluation of STBM and SKAMRT through a simple reporting system supported by cadres; and addressing limited education budgets through collaboration with village funds to reinforce support for STBM and SKAMRT programs and to support the construction of improved, adequate latrine.